Celebrating 400 Years of Ruyl’s Malay Translation of Matthew’s Gospel - Soesilo, Daud (2013)
This paper offers the linguistic, historical, and ecclesiastical background surrounding the first Malay translation of Matthew’s Gospel prepared by the Dutch trader Albert C. Ruyl. It examines the characteristics of his translation, including his use of religious loanwords from Arabic, Portuguese, and Sanskrit, his coining of local terms to render biblical terms for new or foreign concepts, and his cultural adaptations of unknown biblical plants and animals for the sake of the intended readers.
Keywords: Function (skopos); Cultural adaptation; lingua franca; loanwords; theological terms